Using the Taxonomy and the Metrics: What to Study When and Why; Comment on "Metrics and Evaluation Tools for Patient Engagement in Healthcare Organization- and System-Level Decision-Making: A Systematic Review" - Shoshanna Sofaer (Kerman University of Medical Sciences, 2019)
Dukhanin and colleagues' taxonomy of metrics for patient engagement at the organizational and system levels has great potential for supporting more careful and useful evaluations of this ever-growing phenomenon. This commentary highlights the central importance to the taxonomy of metrics assessing the extent of meaningful participation in decision-making by patients, consumers and community members; discusses how the purpose of an evaluation and the organizational relationships among key evaluation stakeholders is likely to influence the choice of metrics in important ways; and suggests a recasting of the metrics in the form of a logic model that supports the selection of metrics that are appropriate for a program given its stage of development and the purposes of the study.